Origami-Inspired Microfluidic Paper-Based Analytical Device (μpad) for Microorganism Detection - Arslan Yıldız, Ahu; Sozmen, A. Baran; Bayraktar, A. Ezgi; Arslan-Yildiz, Ahu (Springernature, 2024)
Pathogenic microorganisms impose great risk especially in resource-limited settings due to inaccessibility of diagnostic tools and monitoring devices. This is mainly caused by current methods often being economically demanding and complex in practice; while these methods are sensitive and accurate, they rarely follow Point-of-care (POC) approaches, which is essential for rapid detection and intervention. Incorporating origami into paper-based analytical devices (mu PAD) presents an innovative alternative, offering affordability, portability, and ease of disposal. Herein, a colorimetric origami mu PAD that is suitable for use in POC applications was developed. The mu PAD was fabricated via laser ablation utilizing PVDF and cellulose membranes. In order to develop the biosensor platform, fabrication parameters were optimized and hydrophilicity of PVDF membranes was improved using various solvents. The PVDF membranes were characterized through light microscopy imaging, protein adsorption assay and contact angle measurements. Then, optimization of the assay parameters was carried out in order to improve sensitivity and resolution of the mu PAD, utilizing Box-Behnken experimental design. The responses generated by the origami mu PAD in form of visible color development were then analyzed using image processing. After optimization is concluded, E. coli detection was carried out as a model system. Resulting calculations showed a limit of detection (LoD) of 2 CFU/mL and a dynamic working range up to 106 CFU/mL for E. coli. Overall, developed origami mu PAD promises an economic advantage compared to conventional methods, and provides rapid and sensitive results without the requirement of expertise or complex equipment.
Sozmen, Alper/0000-0002-2633-3837
Keywords: Microfluidic analytical device; Origami mu PAD; Microorganism detection; Paper-based biosensor